Preclinical Activity of Sacituzumab Govitecan, an Antibody-Drug Conjugate Targeting Trophoblast Cell-Surface Antigen 2 (Trop-2) Linked to the Active Metabolite of Irinotecan (SN-38), in Ovarian Cancer - Perrone, Emanuele; Lopez, Salvatore; Zeybek, Burak; Bellone, Stefania; Bonazzoli, Elena; Pelligra, Silvia; Zammataro, Luca; Manzano, Aranzazu; Manara, Paola; Bianchi, Anna; Buza, Natalia; Tymon-Rosario, Joan; et al. (Frontiers in Oncology, 2020)
Background Epithelial ovarian cancer (EOC) is the most lethal gynecologic malignancy. Sacituzumab govitecan (SG) is a novel antibody-drug-conjugate (ADC) targeting trophoblast-antigen-2 (Trop-2), a cell surface glycoprotein highly expressed in many epithelial tumors, to deliver SN-38, the active metabolite of irinotecan. This study aimed to evaluate Trop-2 expression in EOC tissues and the preclinical activity of SG against primary EOC cell lines and xenografts. Methods Trop-2 expression was assessed in 90 formalin-fixed-paraffin-embedded tumors and 9 primary tumor cell lines by immunohistochemistry (IHC) and flow cytometry, respectively. Trop-2 expression and cell viability after exposure to SG in primary tumor cell lines, non-targeting control ADC, and SG-parental antibody hRS7 were evaluated using flow-cytometry-based-assays. Antibody-dependent-cell-cytotoxicity (ADCC) against Trop-2+ and Trop-2- EOC cell lines was tested in vitro using 4h Chromium-release-assays. In vivo activity of SG was evaluated against Trop-2+ EOC xenografts. Results Moderate-to-strong staining was seen in 47% (42/90) of ovarian tumors by IHC while 89% (8/9) of the primary EOC cell lines overexpressed Trop-2 by flow cytometry. EOC Trop-2+ were significantly more sensitive to SG compared to control ADC (p<0.05). Both SG and hRS7 mediated high ADCC activity against Trop-2+ cell lines. SG also induced significant bystander killing of Trop-2- tumor cells admixed with Trop-2+ EOC cells. In in vivo experiments SG treatment demonstrated impressive anti-tumor activity against chemotherapy-resistant EOC xenografts. Conclusion SG demonstrates remarkable preclinical activity against biologically aggressive and chemotherapy-resistant EOC cell lines and a significant bystander effect against EOC cell lines with heterogenous Trop-2 expression. Clinical trials are warranted.